Resequencing at ≥ 40-fold depth of the parental genomes of a Solanum lycopersicum × S. pimpinellifolium recombinant inbred line population and characterisation of frame-shift InDels that are highly likely to perturb protein function - Kevei, Zoltan; King, Robert C.; Mohareb, Fady R.; Sergeant, Martin J.; Awan, Sajjad Z.; Thompson, Andrew J. (Genetics Society of America, 2015)
A recombinant in-bred line population derived from a cross between Solanum lycopersicum var. cerasiforme (E9) and S. pimpinellifolium (L5) has been used extensively to discover quantitative trait loci (QTL), including those that act via rootstock genotype, however, high-resolution single-nucleotide polymorphism genotyping data for this population are not yet publically available. Next-generation resequencing of parental lines allows the vast majority of polymorphisms to be characterized and used to progress from QTL to causative gene. We sequenced E9 and L5 genomes to 40- and 44-fold depth, respectively, and reads were mapped to the reference Heinz 1706 genome. In L5 there were three clear regions on chromosome 1, chromosome 4, and chromosome 8 with increased rates of polymorphism. Two other regions were highly polymorphic when we compared Heinz 1706 with both E9 and L5 on chromosome 1 and chromosome 10, suggesting that the reference sequence contains a divergent introgression in these locations. We also identified a region on chromosome 4 consistent with an introgression from S. pimpinellifolium into Heinz 1706. A large dataset of polymorphisms for the use in fine-mapping QTL in a specific tomato recombinant in-bred line population was created, including a high density of InDels validated as simple size-based polymerase chain reaction markers. By careful filtering and interpreting the SnpEff prediction tool, we have created a list of genes that are predicted to have highly perturbed protein functions in the E9 and L5 parental lines.
Keywords: Solanum lycopersicum; S. pimpinellifolium; SL2.50; SNP; InDel; introgression; large effect polymorphisms; recombinant inbred lines